The real-life number of neonatal doses of Bacille Calmette-Guérin vaccine in a 20-dose vial - Frederik Schaltz-Buchholzer; Hannah Nørtoft Frankel; Christine Stabell Benn (Taylor & Francis Group, 2017)
Background: Reducing vaccine wastage is important. Bacille Calmette-Guérin (BCG) vaccine is produced in vials of 20 infant doses. The reconstituted vaccine is discarded after 4-6 hours. Therefore, to reduce vaccine wastage, a 20-dose vial of BCG is often only opened if at least 10-12 infants are present, jeopardising BCG vaccination coverage and timely vaccination. We observed that nurses were not able to withdraw 20 doses from the vials and aimed to quantify how many doses could be obtained from these vials by experienced nurses under real-life circumstances. Methods: At the maternity ward of the national hospital in Guinea-Bissau, since 2002 the same two nurses have been vaccinating all eligible children with BCG before discharge. During a month in 2015, within a randomised trial comparing BCG-Denmark and BCG-Russia, we registered how many doses the nurses were able to withdraw from the two types of vaccine vials. Results: The median number of doses which it was possible to withdraw from the vials was 13 (range 11-17): 13 (11-16) for BCG-Denmark (based on 39 vials) and 15 (12-17) for BCG-Russia (based on 29 vials). Conclusions: In real life, experienced nurses could only obtain 13-15 doses from the 20-dose vials. Thus, vaccine wastage is much lower than assumed. Adjusting practice to the real-life number of doses would immediately suggest vials should be opened if 7 rather than 10 infants are present. As other studies have indicated that BCG may have beneficial non-specific effects on overall mortality, the potential gain by opening a 20-dose vial even for one child may be considerable.